Rehabilitation: The health strategy of the 21st century - Gerold Stucki; Jerome Bickenbach; Christoph Gutenbrunner; John Melvin (Medical Journals Sweden, 2017)
There is strong evidence that population ageing and the epidemiological transition to a higher incidence of chronic, non-communicable diseases will continue to profoundly impact societies worldwide, putting more pressure on healthcare systems to respond to the needs of the people they serve. These trends argue for the need to address what matters to people about their health: limitations in their functioning that affect their day-to-day actions and goals in life. From its inception, rehabilitation, 1 of the 4 health strategies identified in the Declaration of Alma Ata in 1978, has had functioning as its outcome of interest. Its practitioners are from fields that include physical and rehabilitation medicine, occupational therapy, physiotherapy, speech and language therapy, orthotics and prosthetics, psychology, and evaluators of functioning interventions, including assistive technologies. Demographic and epidemiological trends suggest that the key indicators of the health of populations will be not merely mortality and morbidity, but functioning as well. This, in turn, suggests that the primary focus of healthcare will need to respond to actual healthcare demands generated by the need for long-term management of chronic conditions, including, in particular, the scaling up and strengthening of rehabilitation. This is the case for thinking that rehabilitation will become the key health strategy of the 21st century.